COVID-19 pandemic effects in people with Autism Spectrum Disorder and their caregivers: Evaluation of social distancing and lockdown impact on mental health and general status - Lugo-Marín, Jorge; Gisbert-Gustemps, Laura; Setien-Ramos, Imanol; Español-Martín, Gemma; Ibañez-Jimenez, Pol; Forner-Puntonet, Mireia; Arteaga-Henríquez, Gara; Soriano-Día, Albert; Duque-Yemail, Juan David; Ramos-Quiroga, Josep Antoni (Research in autism spectrum disorders, 2021)
•COVID-19 pandemic prevention measures (social distancing and lockdown) effects has not been yet studied in ASD population.•ASD level 2 participants showed greater improvement but more treatment adjustments than ASD level 1 after lockdown onset.•Adults with ASD level 1 improved their mental status after lockdown onset, with younger adults showing greater improvement.•Feeding quality improved after lockdown onset in both infant and adult ASD groups.•ASD caregivers increased their stress levels after lockdown onset, while ASD adults reported a decrease in the same outcome. Among the difficulties associated with Autism Spectrum Disorder (ASD) are those related to adaptation to changes and new situations, as well as anxious-depressive symptoms frequently related to excessive environmental requirements. The main objective of this research is to study the psychological impact of the lockdown due to the social emergency situation (COVID-19) in children/adolescents and adults diagnosed with ASD. Participants were 37 caregivers of children/adolescents with ASD, also 35 ASD adults and 32 informants. Evaluation was conducted through a web survey system and included standardized clinical questionnaires (CBCL and SCL-90-R), which were compared with results before lockdown start, and a brief self-reported survey addressing the subjective perception of changes in daily functioning areas. The results revealed a reduction of psychopathological symptoms in both age groups, but only reaching statistical significance in the adult group, except for Somatization, Anxiety, and Obsessive-Compulsive domains. ASD severity Level 2 showed greater improvement after lockdown onset in the children/adolescent group when compared to ASD Level 1 participants. Younger adults (18–25 yoa) reported greater improvement than older adults (=>25 yoa). Survey results indicate an improvement of feeding quality and a reduction in the number of social initiations during the lockdown. Adult ASD participants perceived a decrease in stress levels after the lockdown onset, whereas caregivers reported higher stress levels at the same point in both age groups. Limitations included the small number of participants and a heterogeneous evaluation window between measures. Pyschopathological status after two months of social distancing and lockdown seems to improve in ASD young adult population.